Determination of the Fungicidal Properties of Plants and Herbal Combinations against Ascosphaera Apis l. - Fitrat Yumaguzhin (Journal of Global Pharma Technology, 2016)
The urgency of the problem under investigation is due to the need to develop plant means for the prevention and treatment of fungal diseases in bee colonies. The aim of the article is: * to search for medicinal plants with fungistatic activity in relation to the causative agent of chalkbrood; * to create herbal combinations and to comparatively evaluate their activity in laboratory and production conditions with the chemical compounds recommended for chalkbrood treatment. The main laboratory method for assessing the fungistatic activity of plants and herbal combinations is comparing the zones of delayed growth of the chalkbrood causative agent in experimental and control media. In the production environment, the influence of herbal combinations was assessed by comparing the quality of wintering of bee colonies, the rate of their spring development, the reduction of bee larvae infected with chalkbrood and the amount of collected honey. Laboratory conditions revealed that alcohol extracts of celandine (Chelidonium majus), fir needles (Abietis sibiricae) and pot marigold, or calendula (Calendula officinalis), had a pronounced fungistatic effect (comparable to that of the chemical compounds) on the growth of the mycelium of Ascosphaera apis. Several herbal combinations were prepared which, in vitro, also had a pronounced fungistatic effect. Under their influence, the preservation of bee colonies during wintering was improved, the incidence decreased, and honey production increased. The materials of the article can be of use for scientists working on developing drugs for the prevention and treatment of fungal diseases in bee colonies, as well as for beekeepers who do not use chemical compounds in their produce.Keywords: Medicinal plants, Wintering of bee colonies, Catalase, Spring development, Chalkbrood.